The Influence of Akad Salam Literacy and Customer Trust on Shopee Application Purchase Decisions - Billah, Anisya Al Inayah; Mardiana, Mardiana Mardiana (Fakultas Ekonomi, UIN Maliki Malang, 2025)
This study aims to determine the effect of Akad Salam literacy and customer trust on purchasing decisions on the Shopee application. The study involved 136 Shopee users in Malang City. Data analysis used in this study is multiple linear regression with IBM SPSS Statistics 26. The analysis indicates that Akad Salam literacy has a partially significant impact on purchasing decisions, while customer trust shows a significant influence. This issue arises from a lack of public understanding of the salam contract in online transactions and highlights the importance of trust. The study is novel as it examines how Akad Salam literacy, previously underexplored in e-commerce, combined with customer trust, affects purchasing decisions on a major online platform.